Experimental investigation on the effect of using chemical dyes on the performance of single-slope passive solar still. (February 2022) - Abed, Fayadh M.; Ahmed, Ahmed H.; Hasanuzzaman, M.; Kumar, Laveet; Hamaad, Nasur M.
Highlights: Outdoor performance study of a single-slope solar stills water distillation system. Detailed mathematical model of the single-slope desalination system is developed. The produced water has increased by 40% with using chemical solution. Abstract: Fresh drinking water is the most vital need in human life and climate change is causing scarcity of freshwater resources to fulfil the human and environmental demands. Desalination of saline water is the potential solution to fulfil the scarcity of fresh water. The purpose of this research is to make a comparison between the performances of single-slope solar stills using plain brackish water and with that using chemical dye dozed water for enhancement of freshwater production. In this research, the solar desalination system has been mathematically modelled and experimental investigation was conducted in Tikrit, Iraq, wherein thymol blue and orange methyl were dozed in the saline water to make a comparative evaluation of the distillation efficiency using undozed saline water. Results showed that use of chemical dyes improves the output and efficiency of solar still. The amount of produced water has also increased by 40% with using chemical solution and the highest efficiency was recorded at a depth of 2.5 cm when using thymol blue solution for the months of February (49%) and June (53%). The efficiency was the highest for all altitudes when using thymol blue solution, and the efficiency stood at second place when using the orange methyl solution for the months of February (42%) and June (44%), while the use of water in February and June was only 24% and 26%, respectively. The maximum and minimum output occurred in July (4.25 L/m 2 ·day) and February (0.95 L/m 2 ·day) for the average solar irradiation of 800 W/m 2 and 400 W/m 2, respectively. The quality of distilled water meets all WHO requirements. Distillation facilities like these can help provide fresh water in isolated dry areas that are not coupled to the electrical grid.